The paradoxes of telehealth platforms: what did we learn from the use of telehealth platforms? - Bouabida, Khayreddine; Lebouché, Bertrand; Pomey, Marie-Pascale (Frontiers in Digital Health, 2024)
This article is an overview and reflection of the findings of an evaluative study conducted on a program called “Techno-Covid Partnership” (TCP) implemented in April 2020 at the Centre Hospitalier de l’Université de Montréal (CHUM) in Montreal, Canada. In the context of the COVID-19 pandemic, the CHUM decided in April 2020 to implement telehealth, virtual care, and telemonitoring platforms and technologies to maintain access to care and reduce the risks of contamination and spread of COVID-19 as well as to protect users of health services and health professionals. Three technological platforms for telehealth and remote care and monitoring have been developed, implemented, and evaluated in real-time within the framework of the TCP program. A cross-sectional study was carried out in which a questionnaire was used and administered to users of telehealth platforms including patients and healthcare professionals. The methods and results of the study have been published previously published. In the completion of the two articles published in this context, in this paper, we briefly recall the context of the study and the method performed. The main focus of the paper is on presenting a critical overview and reflection on the major findings of our evaluation of the use of telehealth platforms from the point of view of patients and health professionals and discuss certain paradoxes i.e., the advantages, challenges, recommendations, and other perspectives that emerged in this study.